The Metaphysics of Everydayness and Beyond: Henri Lefebvre – A Critical Reconstruction - Ruhul Amin Mandal (International Journal of Language and Literary Studies, 2026)
The Study investigates the ‘locus’ of the elusive and allusive concept of everyday and everydayness and its ‘telos’ in the fields of metaphysics, cultural study, phenomenology, Marxist socialism, sociology, consumerism and a number of other post structuralism thoughts, by focusing light on marginality and banality of its own state as well as the division of power and distribution of wealth in a particular socio-cultural, political construct in a specified era. The study also explores the conflicting notion of everydayness and questions the truth and validity of its being banal and marginal. The study adopts a qualitative approach, highlighting the fundamental concept of everydayness by drawing on major critical writings in this field, from St. Augustine through Heidegger, Lenin, Althusser, Blanchot, and others to Lefebvre. An analytical study reveals several major issues involving the theory of everydayness, including its elusive nature; conflicting and contradictory ‘locus’; Marxist, sociological orientation that paradoxically negates Marxism itself; consumerism, involving the state and its diverse machineries, and the mercantile class’s direct involvement in it to facilitate the capitalist class as well as people in power and authority. The study also lays bare the innumerable critical and theoretical threads closely linked to the nature and identity of everydayness, as explicated by Lefebvre, from a philosophical viewpoint. The paper contributes to the field of knowledge through its exploration of the idea and identity of ‘everydayness’, which introduces a new concept, although it is linked to Marxist and sociological views. The study also unveils avenues for new prospects and ways to fulfill hope, providing this everyday platform with a place of dignity, honour, and adequacy based on equality and justice. At the same time, it highlights the lacuna and shortcomings, the possible improbability of the dreams of equality and optimism in the coming days, as expected by Lefebvre. The study also contributes to basic knowledge through a keen recognition of the metaphysics of everydayness, depicting the inherent dialectical clashes of oppositions, as well as an evasive and ever-shifting paradigm of ‘transactions’ between everydayness and non-everydayness within the ideological and socio-cultural construct of a society and state in a particular time frame.